Impact of a Rapid Decline in Malaria Transmission on Antimalarial IgG Subclasses and Avidity - Ssewanyana, Isaac; Rek, John; Rodriguez, Isabel; Wu, Lindsey; Arinaitwe, Emmanuel; Nankabirwa, Joaniter I.; Beeson, James G.; Mayanja-Kizza, Harriet; Rosenthal, Philip J.; Dorsey, Grant; Kamya, Moses R.; Drakeley, Chris; et al. (Frontiers in Immunology, 2021)
Understanding how immunity to malaria is affected by declining transmission is important to aid vaccine design and understand disease resurgence. Both IgG subclasses and avidity of antigen-specific responses are important components of an effective immune response. Using a multiplex bead array assay, we measured the total IgG, IgG subclasses, and avidity profiles of responses to 18 P. falciparum blood stage antigens in samples from 160 Ugandans collected at 2 time points during high malaria transmission and 2 time points following a dramatic reduction in transmission. Results demonstrated that, for the antigens tested, (i) the rate of decay of total IgG following infection declined with age and was driven consistently by the decrease in IgG3 and occasionally the decrease in IgG1; (ii) the proportion of IgG3 relative to IgG1 in the absence of infection increased with age; (iii) the increase in avidity index (the strength of association between the antibody and antigen) following infection was largely due to a rapid loss of non-avid compared to avid total IgG; and (iv) both avid and non-avid total IgG in the absence of infection increased with age. Further studies are required to understand the functional differences between IgG1 and IgG3 in order to determine their contribution to the longevity of protective immunity to malaria. Measuring changes in antibody avidity may be a better approach of detecting affinity maturation compared to avidity index due to the differential expansion and contraction of high and low avidity total IgG.